0
$\begingroup$

Given the closed rectifiable curve $\gamma:[0,1]\rightarrow \Bbb C$. we define $-\gamma(t)=\gamma(1-t)$.

I want to prove that $n(\gamma,a)=-n(-\gamma,a).$, where n is the winding number.

Is the following an appropriate proof ? :

I started by using the definition of the winding number

$n(\gamma,a)=\tfrac{1}{2\pi i}\int_{\gamma}\tfrac{dz}{z-a}=\tfrac{1}{2\pi i}\int_0^{2\pi}\tfrac{\gamma'(t)}{\gamma(t)-a}dt=\tfrac{1}{2 \pi i }\int_0^{2\pi}\tfrac{rine^{int}}{re^{int}}dt=n$

(this is obviously circular reasoning though. I think perhaps the following is proof enough )

$-n(-\gamma,a)=-\tfrac{1}{2\pi i}\int_{-\gamma} \tfrac{dz}{z-a}=\tfrac{-1}{2\pi i}\int_0^{2\pi}\tfrac{-\gamma '(t) dt}{-\gamma(t)-a}$

Now recall that $-\gamma(t)=\gamma(1-t)=a+re^{in}e^{-int}$. So

$-n(-\gamma, a)=\tfrac{-1}{2 \pi i}\int_0^{2\pi}\tfrac{-ne^{in}e^{-int}ri}{re^{in}e^{-int}}dt=\tfrac{n}{2\pi} \int^{2 \pi}_0dt=n$

therefore $n(\gamma,a)=-n(-\gamma,a)=n$

What do you guys think is this is a sufficient proof ?

$\endgroup$
1
$\begingroup$

(1) It seems that you only consider the special case $\gamma : [0, 2\pi] \to \mathbb{C},\gamma(t) = a + e^{int}$. But your proof can be adapted to work for any closed piecewise continuously differentiable $\gamma : [a,b] \to \mathbb{C}$. In fact, you have $(-\gamma) = \gamma \circ\iota$, where $\iota : [a,b] \to [a,b], \iota(t) = a + b - t $. Then the chain rule yields $(-\gamma)'(t) = \gamma'(\iota(t))\iota'(t)$. This shows $$\int_a^b\tfrac{\gamma'(t)}{\gamma(t)-a}dt = \int_{\iota(a)}^{\iota(b)}\tfrac{\gamma'(\iota(s))}{\gamma(\iota(s))-a}\iota'(s)ds = \int_{b}^{a}\tfrac{(-\gamma)'(s)}{(-\gamma)(s)-a}ds = - \int_{a}^{b}\tfrac{(-\gamma)'(s)}{(-\gamma)(s)-a}ds$$ which immediately implies $$n(\gamma,a) = - n(-\gamma,a) .$$

(2) You claim that $n(\gamma,a) = - n(-\gamma,a)$ for closed rectifiable curves (which are more general than closed piecewise continuously differentiable curves). This can easily be shown if you write down the definition of $\int_\gamma \tfrac{dz}{z -a}$ for such curves.

$\endgroup$
-1
$\begingroup$

The proof is acceptable and well written. This is not the place to post such questions.

$\endgroup$
  • 2
    $\begingroup$ "This is not the place to post such questions" – I think it is, and there is even a dedicated tag [proof-verification] for such questions. (And if you consider the question off-topic then you should vote to close instead of answering.) $\endgroup$ – Martin R Oct 21 '18 at 19:54

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.